Humanitarian Hypocrisy : Civilian Protection and the Design of Peace Operations - Everett, Andrea L. (Ithaca, NY : Cornell University Press, 2018)
In Humanitarian Hypocrisy, Andrea L. Everett maps the often glaring differences between declared ambitions to protect civilians in conflict zones and the resources committed for doing so. Examining how powerful governments contribute to peace operations and determine how they are designed, Everett argues that ambitions-resources gaps are a form of organized hypocrisy. Her book shows how political compromises lead to disparities between the humanitarian principles leaders proclaim and what their policies are designed to accomplish. When those in power face strong pressure to protect civilians but are worried about the high costs and dangers of intervention, Everett asserts, they allocate insufficient resources or impose excessive operational constraints. The ways in which this can play out are illustrated by Everett's use of original data and in-depth case studies of France in Rwanda, the United States in Darfur, and Australia in East Timor and Aceh. Humanitarian Hypocrisy has a sad lesson: missions that gesture toward the protection of civilians but overlook the most pressing security needs of affected populations can worsen suffering even while the entities who doom those missions to failure assume the moral high ground. This is a must-read book for activists, NGO officials, and policymakers alike.
Frontmatter -- Contents -- Figures and Tables -- Acknowledgments -- Abbreviations -- Introduction -- 1. Devil in the Details -- 2. Political Will, Organized Hypocrisy, and Ambitions-Resources Gaps -- 3. Quantitative Evidence -- 4. France in Rwanda -- 5. The United States in Darfur -- 6. Australia in the Southwest Pacific -- Conclusions and Implications -- Appendix A: The Data -- Appendix B: Statistical Tests -- Notes -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Humanitarian assistance-Case studies; International relief-Case studies; Peacekeeping forces-Case studies; War relief-Case studies; Human Rights; International Studies; POLITICAL SCIENCE / Peace